Religious syncretism and cultural heritage of the Ñuu Savi Jicayán de Tovar - ROSAS-ACEVEDO , Ana Yolanda (Utopía y Praxis Latinoamericana, 2025)
Religious fusion is addressed around the existing social imaginaries of the cultural heritage of the indigenous community. The objective was to analyze religious syncretism through the recovery of the historical memory of the cultural heritage of the Ñuu Na Savi political community from the perspective of symbolic interactionism in territorial settings. Through the ethnographic method, social actors were connected with objects that are part of religious expressions that produce symbols and meanings to understand and describe everyday experiences, local knowledge in the socio-territorial processes of appropriation by the inhabitants. It is crucial to preserve intangible heritage through stewardships to ensure cultural diversity that can strengthen identities and resist the pressures of globalization.